Class warriors [videorecording] - Dormer, Mike.; Fairley, John.; Welfare, Simon ([S.l.] Granite Production for Yorkshire Television, 1990)
Covers Stalin's brutality and ruthless dictatorship by starving peasant and factor workers who do not accept his plan for collective farms.
Credits : Narrator, Sian Phillips ; Editor, Martin Roche.
Keywords: Stalin, Josif -- 1879-1953.; Communist leadership -- Russia; Russia -- Politics and government -- 1925-1953.; Russia -- Social conditions -- 1925-1953.